Inventory management for automotive parts: An application development - Chang, Hao Jie (2023)
This collaborative project with the Department of Mechanical and Materials Engineering (DMME) aims to address the challenges faced by industries in managing their automotive parts inventory. The proposed solution for this project includes developing an inventory management system that includes a web and mobile application to store inventory records. The inventory management system will be integrated with the DMME-designed storage prototype system that is designed to store inventory items. The web application will handle CRUD (Create, Read, Update, Delete) operations to manage inventory data such as product information, stock levels, and reorder levels. The mobile application provides users with the ability to read product details, and update stock levels conveniently and includes a Quick Response (QR) code scanning feature for identifying inventory items and their associated details. As part of the evaluation process, five participants were selected to test the system that includes both the web application and the mobile application. The participants' responses were analyzed to calculate the System Usability Score (SUS), which was found to be 90%. This high score suggests that the inventory management system is highly usable and userfriendly, indicating that it has the potential to improve the management of automotive parts inventory in industries.